Effects of different pulsed vacuum drying strategies on drying kinetics, phenolic composition, and antioxidant capacity of chrysanthemum (Imperial chrysanthemum) - Xu, Huihuang; Wu, Min; Zhang, Tong; Gao, Fei; Zheng, Zhian; Li, Yang (International Journal of Agricultural and Biological Engineering, 2022)
This work aimed to discuss effects of pulsed vacuum drying (PVD) at different temperatures (45°C, 50°C, 55°C and 60°C), vacuum durations (5 min, 10 min and 15 min) and multi-stage heating on drying kinetics, colour attributes, phenolic compounds and antioxidant capacity of chrysanthemum (Imperial chrysanthemum). Results indicated that successive temperature increase reduced the drying time and enhanced the drying rate and moisture diffusivity. Lower temperature (45°C) and the multi-stage (35°C-55°C-60°C) drying presented the superiority in the protection of color, preservation of phytochemical composition (chlorogenic acid, luteolin, total phenolic and total flavonoid content) and improvement of antioxidant capacity (DPPH and FRAP) of chrysanthemum, which was attributed to the low-oxygen drying environment and reduction of thermal degradation losses. Based on the results of drying efficiency and drying quality, the multi-stage heating (35°C-55°C-60°C) has the excellent potential to produce high-quality dried chrysanthemum on a commercial scale. Keywords: pulsed vacuum drying, drying kinetics, chlorogenic acid, luteolin, antioxidant capacity DOI: 10.25165/j.ijabe.20221504.7359 Citation: Xu H H, Wu M, Zhang T, Gao F, Zheng Z A, Li Y. Effects of different pulsed vacuum drying strategies on drying kinetics, phenolic composition, and antioxidant capacity of chrysanthemum (Imperial chrysanthemum). Int J Agric & Biol Eng, 2022; 15(4): 236–242.